2014
DOI: 10.4103/1319-3767.136950
|View full text |Cite
|
Sign up to set email alerts
|

A Korean experience of the use of Boston bowel preparation scale: A valid and reliable instrument for colonoscopy-oriented research

Abstract: Background/Aims:Few bowel preparation scales have been validated. The Boston Bowel Preparation Scale (BBPS) is a novel bowel preparation scale in western countries. We validated the BBPS in Korean patients and assessed the relationship between the colon polyp detection rate and BBPS score.Patients and Methods:This study was a prospective, single-center trial. The BBPS is a 10-point scale that assesses bowel preparation after the completion of all cleansing maneuvers. We assessed three segment scores (the right… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 18 publications
2
26
0
1
Order By: Relevance
“…In a follow-up study, we plan to devise ways to confirm the patients' past bowel preparation methods to allow a more meaningful comparative analysis. Additionally, as BBPS is a validated tool for postwash scoring, it would have been better to use a prewash scoring system, such as the Aronchick Bowel Preparation Scale, along with the BBPS [27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…In a follow-up study, we plan to devise ways to confirm the patients' past bowel preparation methods to allow a more meaningful comparative analysis. Additionally, as BBPS is a validated tool for postwash scoring, it would have been better to use a prewash scoring system, such as the Aronchick Bowel Preparation Scale, along with the BBPS [27][28][29][30].…”
Section: Discussionmentioning
confidence: 99%
“…Little additional benefit of multiple point scales were found with no additional ADR differences between excellent, good and moderate bowel preparation scores 6266 141 150 151 The most widely used scale, the Boston Bowel Preparation Scale,147 152 demonstrated a correlation with ADR where preparation was rated as perfect,153 although this was not confirmed in another recent study 154. No studies directly correlating preparation with PCCRC are available.…”
Section: The Standardsmentioning
confidence: 99%
“…However, the rate of missed adenoma (≤5 mm) in segments with BBPS scores of 2 and 3 has not been studied in detail. Another study (15) reported that higher BBPS scores (≥8 vs. <8) were associated with a higher polyp detection rate (44.9% vs. 33.0%, p=.042). Thus, higher BBPS scores are indicative of a more effective colonoscopy with regard to the likelihood of a prolonged procedure time due to liquid fluid suction, greater difficulty for the colonoscopist, and patient discomfort.…”
Section: Discussionmentioning
confidence: 99%